The Knowledge and the Use of Educational Applications from University Students in Spain and the Czech Republic - Patricia de-Casas-Moreno; Mari-Carmen Caldeiro-Pedreira; Tereza Havránková (Research in Education and Learning Innovation Archives)
Technological evolution has led to many changes at both professional and academic levels. The inclusion of Information and Communication Technologies (ICT) has caused dizzying changes in the different contexts of life (educational, professional, social). More and more applications are being downloaded by users to their mobile devices, both for entertainment and training. For this reason, this study is based on the need to assess the knowledge and attitude of university students towards downloading existing educational applications. In this way, the use and frequency of these tools in the teaching-learning process of the students will be analyzed. In order to carry out this study, the quantitative methodology has been taken into consideration with the collection of data with a sample conformed by a total of 278 students of Higher Education between Spain and the Czech Republic. For this purpose, a survey has been prepared as an instrument of analysis, which has been validated by experts in the field. Among the most outstanding results, it can be seen that in both countries, students download educational apps to a greater or lesser degree, according to their interest and subject matter. Likewise, there is a lack of competences and skills in the use of these new technologies as a training complement. Based on this, we propose the continuous training of students and teachers in the knowledge and pedagogical use of ICT in general and educational apps in particular.